GAMBARAN TINGKAT KEPUASAN PADA PASIEN HEMODIALISA DI RIMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2024 - Rusmauli; Indra Hizkia; Veronica G L Siregar (Poltekkes Kemenkes Medan, 2024)
Background: Hemodialysis (HD) is a kidney replacement therapy that is carried out by flowing blood into an artificial kidney tube (dialyser) which aims to eliminate the remnants of protein metabolism and correct electrolyte balance disorders between the blood compartment and the dialysate compartment through a semipermeable membrane. Hemodialysis is done 2 or 3 times a week for 3-5 hours. The satisfaction of patients undergoing hemodialysis therapy can be created with good service by hospital staff. The achievement of satisfaction in patients undergoing hemodialysis therapy can be assessed based on 5 dimensions in service, namely Service Quality, namely: tangible or tangible, reliability or reliability, responsiveness or responsiveness, assurance or assurance and certainty as well as empathy or care. Objective: To find out an overview of the level of satisfaction in hemodialysis patients. Methods: This study uses a quantitative method where data collection is carried out by questionnaire, with 15 questions. The sampling technique in this study uses total sampling, which uses all existing respondents to be used as informants in data collection, namely 68 respondents. Result: The results of the study showed that the level of satisfaction in tangible hemodialysis patients is satisfied with 39 respondents (57.4%), reliability is satisfied with 40 respondents (58.8%), responsiveness is satisfied with 32 respondents (47.1%), assurance is satisfied with 40 respondents (58.8%), and empathy was satisfied with 50 respondents (73.5%). Conclusions: This shows the level of satisfaction in hemodialysis patients with satisfied results with the services provided. Suggestion: It is hoped that patients can achieve the level of satisfaction according to the desired expectations provided by nurses for services during hemodialysis.